PENETAPAN ASAL USUL ANAK DALAM PERSPEKTIF MAQASID SYARI’AH: ANALISIS PERBANDINGAN PUTUSAN PENGADILAN AGAMA BOGOR DAN CIBINONG - Eva Ae Dunuraeni; A. Suganda; Encep Taufik Rahman (Jurnal Pelita Nusa, 2026)
This study examines the legal determination of a child's lineage (itsbat nasab) from the perspective of maqasid al-shari'ah through a comparative analysis of Decision No. 174/Pdt.P/2024/PA.Bgr and Decision No. 868/Pdt.P/2024/PA.Cbn of the Religious Courts, which reached different conclusions in cases involving similar legal issues. The disparity reflects differing judicial approaches to protecting children's legal rights. This research aims to compare the “ratio decidendi” of both decisions and evaluate their conformity with the objectives of maqasid al-shari'ah, particularly hifz al-nasl (protection of lineage) and hifz al-nafs (protection of life and human dignity). A normative juridical approach with a comparative case study method was employed by analysing court decisions, statutory regulations, and relevant legal literature. The findings indicate that a formalistic and procedural approach tends to limit the protection of children's rights, whereas a substantive approach provides greater legal certainty regarding a child's legal status, identity, and civil rights. Therefore, integrating maqasid al-shari'ah into judicial reasoning is essential to ensuring that judicial decisions promote not only legal certainty but also substantive justice and comprehensive protection of children's rights within Indonesia's Islamic family law system.